Computational fluid dynamics modelling of airflow and carbon dioxide distribution inside a seminar room for sensor placement. (October 2022) - Mou, Jianqiang; Cui, Shan; Khoo, David Wee Yang
Abstract: Demand control ventilation (DCV) is a high energy efficiency ventilation strategy with control input from carbon dioxide (CO2 ) sensors. The measurement data quality of CO2 sensors plays a critical role in accurate determination of the indoor air quality (IAQ) and actual ventilation rate in implementation of the DCV. In this paper, the airflow field and CO2 spatial distribution in an indoor space of a seminar room seated with breathing occupants was modelled and simulated utilizing computational fluid dynamics (CFD) analysis. The airflow streamlines, airflow pressure and velocity, turbulence kinematic energy, as well as the CO2 spatial distribution in the seminar room were investigated. The locations for proper placement of the CO2 sensors in the seminar room were identified, for assuring the measurement data quality and effective DCV to achieve high energy efficiency.